Kinetic modeling of azo dyes photocatalytic degradation in aqueous TiO2 suspensions. Toxicity and biodegradability evaluation - Satuf, María Lucila (2011)
A kinetic model of the photocatalytic degradation of the azo dye Acid Orange 7 (AO7) is presented. It is based on mechanistic reaction steps and includes the modeling of the radiation absorption effects. The evaluation of the radiation field inside the reactor was a hieved by solving the radiative transfer equation for the heterogeneous system. The study was carried out in a slurry batch photoreactor with recycle, employing artificial UV light as the source of radiation and TiO2 Degussa P25 as catalyst. The biodegradability and toxicity of the irradiated mixture was also assessed. The kinetic model satisfactorily represents the evolution of AO7 under different experimental conditions, with a root mean square error of the estimations of 13.9%. The biodegradability of the AO7 solution was considerably enhanced after the photocatalytic treatment. In addition, a clear reduction of the toxicity of the azo dye was achieved at the end of the experiments.